2009
DOI: 10.1515/mamm.2009.005
|View full text |Cite
|
Sign up to set email alerts
|

A molecular and chromosomal study of the moonshine shrew, Crocidura luna Dollman, 1910 from Zambia with a description of a new remarkable karyotype

Abstract: A molecular and chromosomal study of the moonshine shrew, Crocidura luna Dollman, 1910 from Zambia with a description of a new remarkable karyotype AbstractThe genus Crocidura Wagler, 1832 represents the most diverse group of Soricidae. It is widely accepted that the genus is in need of revision, because the taxonomy of several species is still unresolved. In this paper, we present a chromosomal (standard and G-banding) and molecular genetic (16S rDNA, 1112bp; cytochrome b, 501bp) characterization of specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Chinese: 新月麝鼩. With more than one species, this complex needs taxonomic revision (Castiglia et al, 2009). Recorded from NE DR Congo, Uganda, Kenya, most of Tanzania, Zambia, SE DR Congo, WC Mozambique, Malawi and Mozambique.…”
Section: Checklist Of Mammalsmentioning
confidence: 99%
“…Chinese: 新月麝鼩. With more than one species, this complex needs taxonomic revision (Castiglia et al, 2009). Recorded from NE DR Congo, Uganda, Kenya, most of Tanzania, Zambia, SE DR Congo, WC Mozambique, Malawi and Mozambique.…”
Section: Checklist Of Mammalsmentioning
confidence: 99%
“…Initial studies based on nuclear and mitochondrial sequences (mtDNA) suggested a common ancestry of all Crocidura species [15,16], with a clear dichotomy between Afrotropical and Palearctic taxa, which display contrasting patterns of chromosomal differentiation [17]. With the exception of C. luna (2n = 28 or 36 [18]) Afrotropical species are characterized by high diploid numbers (from 2n = 42 to 2n = 68), 2n = 50 being the most common chromosomal form. Palearctic species, on the other hand, present a tendency for low diploid numbers (from 2n = 22 to 2n = 42, [17], with 2n = 40 as the predominant karyotype.…”
Section: Introductionmentioning
confidence: 99%